Corporate Social Responsibility and Firms Ability to Collude - Luca Lambertini; Alessandro Tampieri (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2011)
We examine a duopoly with polluting production where firms adopt a form of corporate social responsibility (CSR) to define their objective functions. Our analysis focuses on the bearings of CSR on collusion over an infinite horizon, sustained by either grim trigger strategies or optimal punishments. Our results suggest that assigning a weight to consumer surplus has a pro-competitive effect under both full and partial collusion. Conversely, a higher impact of productivity on pollution has an anti-competitive effect under partial collusion, while exerting no effect under full collusion. Under partial collusion, the analysis of the isoquant map of the cartel reveals that complementarity arises between the two weights.
Keywords: H23; L13; L41; 330